Éclairer les mathématiques par les exemples ? - Alain Kuzniak; Marc Rogalski; Laurent Vivier (Recherches en Éducation)
The strong link between mathematics and examples is analysed as a very component of mathematical activity. Then some didactical tentative proposals are presented for developing mathematical training based on a reasoned use of examples. Interviews with researcher-teachers enable to identify different types of using examples at a universitary level in the French context. In fact examples are considerd as a crucial element that is necessary for conducing efficient mathematical work, including for students; nevertheless, their use remains marginal in mathematical teachers’ practives: their teaching privileges grand theoretical constructions and their emblematic theorems.